Study on the Effect of Agricultural Technological Progress on Agricultural Carbon emission effectualness - Xinqi Ge (Forest Chemicals Review)
The fourth assessment report released by the IPCC in the year of 2007 pointed out that agricultural production is the second largest source of global greenhouse gas emissions, and agricultural carbon emissions are gradually attracting attention. To reduce agricultural input and carbon effectualness, it is mainly necessary to improve the effectualness of agricultural carbon emissions, while the progress in agricultural technology has the greatest impact on the effectualness of agricultural carbon emission. This study took the Statistical Yearbook of Xinjiang Production and Construction Corps from 1998 to 2017 as the data source, and took 13 divisions of the Corps as samples, using the threshold panel model to test the nonlinear relationship between agricultural technological progress and agricultural carbon emission effectualness, and further estimated the partial effect by using generalized least squares (FGLS).The study found that there is threshold level of human capital and agricultural economic development effect. Under different levels of human capital and the threshold conditions of agricultural economic development stage, the impact of agricultural technological progress on agricultural carbon emission effectualness is significantly different. There is a nonlinear relationship between the two, and there is a partial effect on the degree of agricultural carbon emission effectualness.